2015
DOI: 10.1007/s00535-015-1071-2
|View full text |Cite
|
Sign up to set email alerts
|

The value of systematic lymph node dissection for intrahepatic cholangiocarcinoma from the viewpoint of liver lymphatics

Abstract: Lymph node (LN) metastasis from intrahepatic cholangiocarcinoma (IHCC) might be one of the most important indicators of aggressive surgical resection, yet the value of LN dissection is still controversial. To address this clinical problem, we need to better understand the multidirectional lymphatic outflow from the liver. Although most hepatic lymph flows into the hilar LNs along portal triads, there are also several lymphatic outflows directly communicating with distant areas or the general lymphatic system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 71 publications
(67 reference statements)
0
46
1
Order By: Relevance
“…However, systematic lymphadenectomy may improve the outcomes of ICC if we identify the location of lymphatic metastasis 13 . Some researchers recommend that ICC patients without LNM should not undergo routine LND, and extended systemic LND is not recommended for ICC patients with LNM 14 . Therefore, this study analyzed LND and LNM as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…However, systematic lymphadenectomy may improve the outcomes of ICC if we identify the location of lymphatic metastasis 13 . Some researchers recommend that ICC patients without LNM should not undergo routine LND, and extended systemic LND is not recommended for ICC patients with LNM 14 . Therefore, this study analyzed LND and LNM as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Cholangiocarcinoma is a rare malignant disease associated with a poor prognosis . Recent advancements in medical imaging techniques have led to an increase in the number of patients diagnosed with cholangiocarcinoma, with a higher incidence in East Asia . Operation at the early stage of the disease is the only curative option; however, most patients are diagnosed at advanced stages despite improvements in medical imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Operation at the early stage of the disease is the only curative option; however, most patients are diagnosed at advanced stages despite improvements in medical imaging techniques. Patients with metastatic cholangiocarcinoma have a particularly high risk for mortality, with a median survival of 8‐12 months even with combined modality therapy . A novel therapeutic approach is needed to improve the prognosis of cholangiocarcinoma patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have identified patient and disease characteristics such as age at diagnosis, number of tumors, tumor size, and invasion of adjacent structures to be predictive of poor overall survival . More recently, several reports have also identified nodal status as a potentially useful prognostic indicator for ICC . However, the role of lymphadenectomy remains controversial and poorly defined with contrasting views between Eastern and Western centers .…”
Section: Introductionmentioning
confidence: 99%